A 13‐year‐old soccer player presenting with a Morel‐Lavallee lesion of the knee: A case report and review of literature - Nicholas R. Williams; Alvarho J. Guzman; Patrick Waldron; Ethan Vallelanes; Samantha J. Cheng; James L. Chen (Clinical Case Reports)
Key Clinical Message Morel‐Lavallee lesions are uncommon injuries and there is a lack of data to support what the most effective management is. In the case of a young athlete with a small lesion, we propose that conservative treatment with rest and close follow up is appropriate.